Organizational Cybernetics and Human Values - Ericson, Richard F. (Academy of Management Journal, 1970)
The major hypothesis explored by this paper is that managers of large enterprises?public or private, in any context ?have an increasingly urgent socio-humanistic responsibility to create self-actualizing organizations which will assure to the maximum extent possible, the transcendence of human values. The major thesis of the paper is that general systems insights, cybernetic science and computer technology provide the basis for achievement of this paramount objective. Over two decades ago Norbert Wiener depicted the human degredation potentially inherent in the cybernetic approach to organizational and institutional design. The substance of such concerns may perhaps now be encapsulated by the question: Are we presently pursuing a witless decision path where the sole parameter is ?What is possible technologically?? as we yesterday appeared only to ask, ?Does it make sense economically??